2020
DOI: 10.4314/ahs.v20i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and biochemical assessments as early prediction of polycystic ovarian syndrome in obese women

Abstract: Backgroud: Polycystic ovary syndrome (PCOS) is considered as a common cause of hormonal disturbance and obesity. The diagnosis of PCOS was done by different methods including clinical signs as anovulation, hyperandrogenism, biochem- ical markers and ultrasounographic investigation. This study investigated comparative outcomes of ultrasonographic and biochemical markers for early prediction of PCOS in obese women. Subjects and methods: Seventy-five patients were clinically diagnosed with obese, PCOS and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Additionally, recent research has suggested using more markers for the early prediction of PCOS. Thus, levels of DHEA (dehydroepiandrosterone), insulin, HbA1c (glycosylated haemoglobin) and LDL-c (low-density lipoprotein-cholesterol) could be used for the early diagnosis of PCOS [ 69 ]. Xenin, an ancient regulatory peptide [ 70 ] known as a regulator of insulin and glucagon secretion (thereby an important therapeutic target in DM and obesity [ 71 ]), was also shown to be a factor of PCOS pathogenesis [ 72 ].…”
Section: Novel Markers For Pcos Diagnosismentioning
confidence: 99%
“…Additionally, recent research has suggested using more markers for the early prediction of PCOS. Thus, levels of DHEA (dehydroepiandrosterone), insulin, HbA1c (glycosylated haemoglobin) and LDL-c (low-density lipoprotein-cholesterol) could be used for the early diagnosis of PCOS [ 69 ]. Xenin, an ancient regulatory peptide [ 70 ] known as a regulator of insulin and glucagon secretion (thereby an important therapeutic target in DM and obesity [ 71 ]), was also shown to be a factor of PCOS pathogenesis [ 72 ].…”
Section: Novel Markers For Pcos Diagnosismentioning
confidence: 99%
“…A similar study found a positive association between mean ovarian volume and WHR 27 . Another recent study reported that the mean ovarian volume was statistically higher in obese PCOS cases as compared to non-obese counterparts 28 . A similar study reported a significant increase in ovarian volume and the number of ovarian follicles (<9 mm) on ultrasound in PCOS cases as compared to controls 29 .…”
Section: Discussionmentioning
confidence: 92%